Mitigation of ionospheric scintillations for GPS signals under geomagnetic storm conditions using LMS adaptive filter. (2016) - Sridhar, M.; Raju, K. Padma; Rao, Ch. Srinivasa; Ratnam, D. Venkata
Ionospheric scintillation, an effect due to the electron content density irregularities, is one of the various phenomena of ionosphere that causes deep and rapid signal fading. Scintillations not only cause deep signal fading, but also affect GPS/satellite-based augmentation (SBAS) receiver pseudo range and carrier measurements. As India comes under the low latitude region, more care has to be taken for providing ionospheric differential corrections to GPS users. GPS data collected at KL University (Geographic 16.31°N, 80.37°E) Vaddeswaram, India is considered for the analysis. This location falls under the transition zone between the equatorial trough and the anomaly crest in Indian region. In this paper, spectral analysis of amplitude and phase scintillations is carried out during intense geomagnetic storms, occurred during the period 2013-2014. Statistical parameters of the GPS signal such as scintillation index and power spectral density (PSD) are discussed. LMS adaptive filter turns to be the appropriate filter in mitigating the scintillations. These results would be very much useful for developing a suitable model for ionospheric scintillation for the location.